Uvular injury during the perioperative period in patients undergoing general anesthesia. (22nd October 2013) - Pamnani, Anup; Faggiani, Susan L.; Hood, Melanie; Kacker, Ashutosh; Gadalla, Farida
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to evaluate the incidence and causes of uvular injury in the patients that received general anesthesia in the perioperative period. Study Design A 4‐year retrospective review of cases of uvular injury and their resolution was conducted in adult patients who received general anesthesia at our institution. Methods An extensive review was conducted of the quality assurance (QA) database maintained by the Department of Anesthesiology at our tertiary academic medical center. The database was searched for cases of uvular injury that occurred in adult patients undergoing general anesthesia that between January 2007 and December 2010. The medical records of identified patients were then obtained to evaluate the presentation, treatment and ultimate resolution of injury. Results Ten cases of uvular injury were reported in the 28, 788 general anesthetics conducted over a 3‐year period in adult patients. This correlates to an incidence of 0.034%. Uvular injury occurred in mostly male patients (80%) during elective cases in the supine position. All cases were associated with endotracheal intubation. Additional objects, such as gastric tubes and esophageal temperature probes, were placed in the pharynx of 80% of these patients. Urologic procedures were associated with 50% of reported cases. Treatment ranged from observation to medical therapy. There were no permanent symptoms in any of the patients. Conclusion Uvular injury is a relatively rare complication that occurs in patients during the perioperative period who receive general anesthesia. While endotracheal intubation is closely associated with this type of injury, further study is required to elucidate the mechanism and other associated etiologic factors. Level of Evidence 4. Laryngoscope, 124:196–200, 2014